New short T6 heat treatments for aluminium silicon alloys obtained by semisolid forming - Menargues, S.; Martín, E.; Baile, M.T.; Picas, J.A. (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2015)
In this work the heat treatment response of SSM processed A356 and A357 casting alloys was analysed. The development of a new T6 heat treatment, with solution times less than 30min has been allowed . In this new short heat treatment, the alloy showed better mechanical properties compared to the same alloy which heat treated in standard conditions (solution time between 6h and 8h). This new heat treatment, carried out at the solution temperature of 540°C, enabled the complete magnesium dissolution, while minimizing the grain growth of the α-phase and the eutectic silicon. Although this experiment was carried out on A356 and A357 aluminium alloys, conformed by Sub-Liquidus-Casting process (SLC), the results may be applied to the components produced with other semi-solid technologies or others Al–Si hardenable alloys that form coherent magnesium inter-metallic precipitates.